Early Implementation of Active Surveillance on Detection of Carbapenemase-Producing Enterobacteriaceae. (4th October 2017) - Yagi, Tetsuya; Iguchi, Mitsutaka; Tetsuka, Nobuyuki; Morioka, Hiroshi; Matsumoto, Akane; Hiroki, Kato; Tomita, Yuka
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) is increasing worldwide and becoming a great concern in the clinical settings. In Japan, national surveillance for CRE has been established and the cases diagnosed as having infectious diseases caused by CRE were determined to be notified since September 2014. Among CRE, carbapenemase-producing Enterobacteriaceae (CPE) has particular importance in terms of infection control because of the spread of plasmids carrying a carbapenemase gene among other Enterobacteriaceae. Early detection of CPE and implementation of strict infection control measures are essential to control the spread of this multidrug-resistant organisms. Methods: CRE was detected in the criteria of either cefmetazole–MIC ≥ 64 µg/mL and imipenem–MIC ≥ 2 µg/mL, or meropenem–MIC ≥2 µg/mL. CPE was identified using phenotypic method with β-lactamase inhibitors, clavulanic acid, boronic acid, and sodium mercaptoacetic acid. Once CPE was detected, colonization or infectious disease, active surveillance culture (ASC) with feces or rectal swabs among patients in the same ward of index case was conducted to find asymptomatic colonization together with strict cantact precautions. ASC was done using CHROMagar™ ESBL (KANTO KAGAKU, Japan) and compared with CDC-recommended method. ASC was repeated once a week until no new colonizer was found with two consecutive ASC. Results: With the CHROMagar™ ESBL-method, we could detect four CRE isolates 1 day earlier than the CDC method which could detect three CRE isolates using the same 53 samples (Figure 1 and Table 1). From September 2014 to December 2016, 64 CRE were isolated from clinical samples, and there were 14 cases, including five cases of infectious diseases, of implementation of ASC as a part of stringent infection control measures mainly because of the detection of E. cloacae CPE (Table 2). New asymptomatic CPE colonizers were detected in only two cases, and non-CPE CRE colonizers were detected in one case. Conclusion: Early implementation of ASC on detection of CPE as a part of stringent contact precautions contributed to prevent further spread of CPE. Disclosures: All authors: No reported disclosures.